2013
DOI: 10.5902/217976927538
|View full text |Cite
|
Sign up to set email alerts
|

Adoecimento e uso de medicamentos psicoativos entre trabalhadores de enfermagem de unidades de terapia intensiva

Abstract: RESUMO: Objetivo: identificar o adoecimento e uso de medicamentos psicoativos entre trabalhadores de enfermagem de Unidades de Terapia Intensiva. Método: estudo descritivo com abordagem quantitativa, realizado em Unidades de Terapia Intensiva Pediátrica, Neonatal e Adulto de um hospital de ensino no segundo semestre de 2011, com participação de 49 trabalhadores de enfermagem. O instrumento foi um questionário autoaplicável, com análise por meio de estatística descritiva simples. Resultados: 28,5% dos trabalhad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
2
17

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 6 publications
1
25
2
17
Order By: Relevance
“…As for marital status, there is a higher prevalence of depression in people who do not have close interpersonal relationships, without children, or who are separated or divorced (13) . Studies carried out with nursing staff working in an intensive care unit showed that the prevalence of depressive symptoms is higher in professionals working in the night shift and that there was a significant association between depressive symptoms and work shift (13,(22)(23)(24) , a contradictory result to this (1) : using Pearson's correlation test. Burnout and depressive symptoms in intensive care nurses: relationship analysis Vasconcelos EM, Martino MMF, França SPS research.…”
Section: Discussionmentioning
confidence: 99%
“…As for marital status, there is a higher prevalence of depression in people who do not have close interpersonal relationships, without children, or who are separated or divorced (13) . Studies carried out with nursing staff working in an intensive care unit showed that the prevalence of depressive symptoms is higher in professionals working in the night shift and that there was a significant association between depressive symptoms and work shift (13,(22)(23)(24) , a contradictory result to this (1) : using Pearson's correlation test. Burnout and depressive symptoms in intensive care nurses: relationship analysis Vasconcelos EM, Martino MMF, França SPS research.…”
Section: Discussionmentioning
confidence: 99%
“…3 It is characterized by variations of mood and perpetuation of depressive symptoms including need for isolation, despondency, sadness, fatigue, insomnia, concentration difficulties, anxiety, fear, guilt, slowness, apathy, alterations to judge the truth, alterations of appetite, and presence of negative and recurrent thoughts. [3][4][5][6] Affected individuals, family members, friends, and the community experience intense suffering. 7 This disease, 1 is considered a public health problem.…”
Section: Introductionmentioning
confidence: 99%
“…Depression is one of the three most prevalent psychic illnesses in these workers, who daily deal with human suffering, pain, Joy, sadness and need to offer help to those who require their care. 1,5,6 Understanding depression among nurses who work in intensive care unit, as well as the risk factors involved, is important for researchers working primarily in the area of worker health. 6 The literature shows the sickness of these professionals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations